Toward Learning Tools: Analyzing Precision of Tool Maker and Optical Comparator - Gracilla, Salvador; Angelo Henry ABELLAR; Marvin CENIDOZA; Christian Russel CERZO; Kim Laurence Del AGUA; John Michael Ton R. ENDOZO; John Rick HAPITA; August G. IGAT; Aldrin MAÑALAC; Jason Pamilacan; Cyrus Vrylle QUINTOS; Aivhan John QUILONDRINO; Marie Jo Tess RAGOS; Cynic TENEDERO; Leon MENDIGORIN (RADINKA JAYA UTAMA PUBLISHER, 2024)
This paper aims to provide a clear analysis to choose what is the best tool for their specific needs. This is a quantitative descriptive correlation study that determines the difference in terms of accuracy and precision of optical comparator and toolmaker. Two different materials were measured using an optical comparator and tool maker microscope at the Technological University of the Philippines Manila Campus. Technological University of the Philippines is one of the schools in the Philippines that uses the equipment. Two measuring machines can be located at the College of Industrial Technology (CIT), Mechanical Engineering Technology Department (MET). This location was chosen for its highly efficient and calibrated machines to come up with accurate results. Both machines are significantly useful to industry and companies. Toolmaker microscope is a bit complicated while optical comparator has very slight difference to its measurements. However, the optical comparator is less costly than that of a toolmaker’s microscope. This paper has navigated the complexity of both tool maker's microscope and optical comparators that offer great accuracy and precision in terms of measuring small components that are used in the manufacturing process to make products.